Analisis Impelementasi Konsep Pembelajaran Diferensiasi Dalam Mata Pelajaran Biologi Pada Era Digital 4.0 di Kelas X - Siti Anindya Putri; Aulya Nanda Prafitasari (ScienceEdu, 2023)
Learning is basically the interaction of students with their learning environment so that there is an impact in the form of changes in behavior for a better direction. The learning process is an integrated and organized process in the teaching and learning process activities, there are active interaction between teachers and students when learning takes place. Furthermore, support interactive learning as a teacher, it is necessary to develop a variety of learning media and learning tools following the development of technology and times which are increasingly sophisticated and varied educational platforms provided. Along with the development of an increasingly sophisticated era and all human activities are facilitated by the rapid development of technology. In Digital Era 4.0, many people have become consumptive in using smartphones and smart devices. It is undeniable that this also happens to most students today. Therefore, as educators, we must address this phenomenon by making smartphones and smart devices as learning media that make it easier for them to learn and can create a pleasant learning environment. Differentiated learning is one of the strategies in the independent curriculum that an educator can use to meet the needs of each learner. Differentiation is a process of teaching and learning activities where learners learn material based on their learning styles, abilities, and the needs of each learner so as to form fun and meaningful learning during the process of learning activities.